ISLAM DAN TRADISI LOKAL DALAM PERSPEKTIF MULTIKULTURALISME - M. Zainal Abidin (Millah: Journal of Religious Studies, 2009)
This paper tries to explore the compatibility of Islam toward the idea of multiculturalism. The discussion about the relationship between Islam and multiculturalism is very important in the context of plural country such as Indonesia, whether in religion side or in culture one. Knowing the significance of multiculturalism, the question is, how far the compability of Islam as mayor religion in this country with the idea of multiculturalism. As for the writer, there are two ways in making the compatibility of Islam toward the idea of multiculturalism: Firstly, that we need to reinterpret the orthodox religion doctrine that always exclusive and oppressive. The reinterpretation is done in order religion may accept the local tradition wisdom. Secondly, that we always need to have a dialogue between Islam and the modernity. In multicultural perspective, it’s clear that that the existence of local tradition will enrich the Islamic civilization. Each local tradition has the legal position before Islam. Here, the idea of “pribumisasi Islam” in Indonesia context as stated by Gus Dur is in the same way with the idea of multiculturalism.